Historia Dilemma Pendidikan Islam: Mengutamakan Kesalehan dan Moral atau Prestasi Akademik atau Integrasi Keduanya dalam Pembelajaran yang Berpusat pada Siswa - Syu'aib Nawawi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The purpose of this article is to examine historically the dilemma of Islamic Education in practice prioritizing piety and morals or academic achievement or the integration of both and whether student-centered learning comes from the concept of Islam. The results of the discussion concluded that the progress and decline of Islamic education along with political and other developments in each era of large-scale gradations began the attack of the orientalist era of Al Ghozali, external invasion had attacked the heart of Islam which began from the continuous 11th and 12th crusades and Mongol invasion during the 13th century, and afterwards, Islamic education underwent several transformations in its main characteristics even though it was slowed down by the issue of taqlid. The point is the combination of the deadly taqlid invasion and foreign attacks significantly dims the prominence of Islam in the artistic and scientific world. Between the emergence of the appearance of Islamic thinkers and their relationship with the rulers of their time, differences must be made between Madrasahs and Maktab because both are related to Islamic education. Islam regards science as another form of worship and that humans must be close to Allah. Science studies are expected to strengthen faith: